Living among the Duce's words: the visual materialization of political rhetoric in Italian public space, from the Risorgimento to Fascism. Issue 3 (3rd July 2018) - versari, maria elena
Abstract: This article is devoted to the use of political inscriptions in Italy from the Risorgimento to Fascism. More specifically, it addresses the way in which Fascism appropriated and reworked a tradition of civic and patriotic epigraphs established in the nineteenth century, during Italy's struggle for independence and in its aftermath. By doing so, it aims to correct the common assumption that Fascism's use of spectacular monumental strategies aimed at the mere dismissal of real political content through its aestheticization, and to clarify the way in which Benito Mussolini's regime instead engaged in a cunning historiographical reassessment of Italy's recent past and its material history.